Dwelling in contradictions: Deep maps and the memories of Jews from Libya - Rossetto, Piera (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2017)
The article deals with performances of memories and identities by and about Jews from the Middle East and North Africa region, with a focus on Jews of Libyan descent. It acknowledges the complexity that intrinsically characterizes these sources in terms of the heterogeneity of their contents, but also the political implications inherent to their transmission and communication. What is needed, however, is to make this complexity readable, and to make it readable, the author suggests making it visible. To achieve this goal, the author proposes adopting a new research approach which takes inspiration from the field of digital humanities, to assist in thinking spatially and visually about the performances of memories and identities. This can bring about a kind of methodological reconciliation between the researcher, the complexity of the data, the necessity to transform them into accurate research results and the responsibility to effectively communicate them to the larger public.